Pengaruh Industrialisasi Terhadap Emisi CO2 Di Indonesia - Aldodi Pratama (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Developing countries such as Indonesia have the ambition to carry out structural transformations in order to increase their economic growth. The structural transformation of the economy from low-productivity agriculture to high-productivity industrialization is seen as a prerequisite for achieving sustainable economic growth, but there are concerns about the impact of industrialization on the environment, especially in the context of carbon emissions and climate change. This study aims to analyze the effect of industrialization on long-term and short-term CO2 emissions in Indonesia, using the Vector Error Correction Model (VECM) method on time series data in Indonesia for the period 1974-2016. The variables used in this study are CO2 emissions, carbon intensity, energy intensity, Gross Domestic Product (GDP) and industrial value added, where the CO2 emission variable is the endogenous variable and the industrial value added variable is a proxy for industrialization. The other variables refer to the rich identity theory which describes the similarity of the relationship between human activities and the environment. The results of the study indicate that there is a significant positive effect of carbon intensity, energy intensity and GDP on CO2 emission in Indonesia in the long term, meanwhile the value added industry show a significant negative effect in the long term. These variables further show no significant effect on CO2 emissions in the short term.Keywords: Industrialization, CO2 Emissions, Structural Transformation, Vector.Error, Correction Model (VECM), Granger Causality Test